Legal Protection for Online Fraud Victims in the Context of Inclusive Digital Transformation in Indonesia (Universitas Terbuka, 2025)
This study analyzes the legal protection framework for online fraud victims amidst the rapid digital transformation in Indonesia. Although digital development has fostered inclusive economic growth, it has also increased the public's vulnerability to cybercrime. This research finds that the existing legal framework, namely the Electronic Information and Transactions Law (UU ITE) and the Criminal Code (KUHP), remains partial and ineffective in ensuring the restoration of victims' rights. The current regulations primarily focus on criminal aspects and sanctions for perpetrators, while the mechanism for restitution or compensation for victims is often unclear and difficult to access. This research employs a normative legal research method with a descriptive-analytical approach, applying both a statute approach and a conceptual approach. Primary and secondary legal materials were analyzed qualitatively to identify legal gaps and formulate an ideal protection model. The analysis results show that victims face significant challenges in accessing justice, such as difficulties in evidence collection and perpetrator tracing, the low capacity of law enforcement officials, and limited public digital literacy. To address these issues, this article proposes a multidimensional solution. First, regulatory reforms are needed to focus on victims' rights and establish a more explicit duty of care for digital service providers. Second, enhancing the capacity of law enforcement in digital forensics and inter-agency collaboration is essential. Third, a stronger collaboration among the government, the private sector, and the public is required to build an integrated case reporting and handling system. Finally, inclusive digital transformation, supported by massive digital literacy campaigns, must serve as a fundamental foundation for creating a safe and equitable digital space for all citizens.